Steroid, thiamine, and ascorbic acid during post-resuscitation period for comatose out-of-hospital cardiac arrest survivors (STAR) trial: Protocol for a clinical trial - Youn-Jung Kim; Byuk Sung Ko; Young-Il Roh; Yong Hwan Kim; Won Young Kim (PLoS ONE, 2025)
Background Systemic ischemic-reperfusion injury following cardiac arrest results in multisystem organ failure, brain injury and death. The aim of this trial is to investigate whether the combined use of cortisol, ascorbic acid (vitamin C), and thiamine during the early post-resuscitation period reduces the neurologic injury among out-of-hospital cardiac arrest (OHCA) survivors treated with targeted temperature management (TTM). Method This is a single-blind, multi-center, randomized, placebo-controlled trial to be conducted in nine tertiary university-affiliated hospitals in South Korea. A total of 160 OHCA survivors treated with TTM will be randomly assigned to the treatment or control groups (1:1 ratio). For the treatment group, patients will intravenously receive a combination dose of ascorbic acid (50 mg/kg, maximum single dose 3 g), thiamine (200 mg), and cortisol (100 mg) that will be mixed in three separate 50mL bags of 0.9% saline, respectively, every 12 hours for 3 days. For the placebo group, patients will receive three separate 50mL bags of 0.9% saline intravenously in the same manner. The primary outcome is the peak neuron-specific enolase level at 48–72 hours after the return of spontaneous circulation. Discussion The potential benefits of ascorbic acid, thiamine, and cortisol as neuroprotective agents have been reported in previous preclinical trials. This trial is the first clinical trial to assess the neuroprotective effectiveness of a combination of ascorbic acid, thiamine, and cortisol for OHCA survivors. Trial registration ClinicalTrials.gov NCT04921189